Quantification of joint mobility limitation in adult type 1 diabetes - Phatak, Sanat; Mahadevkar, Pranav; Chaudhari, Kaustubh Suresh; Chakladar, Shreya; Jain, Swasti; Dhadge, Smita; Jadhav, Sarita; Shah, Rohan; Bhalerao, Aboli; Patil, Anupama; Ingram, Jennifer L.; Goel, Pranay; et al. (Frontiers in Endocrinology, 2023)
Aims: Diabetic cheiroarthropathies limit hand mobility due to fibrosis and could be markers of a global profibrotic trajectory. Heterogeneity in definitions and lack of a method to measure it complicates studying associations with organ involvement and treatment outcomes. We measured metacarpophalangeal (MCP) joint extension as a metric and describe magnetic resonance (MR) imaging determinants of MCP restriction.Methods: Adults with type 1 diabetes were screened for hand manifestations using a symptom questionnaire, clinical examination, function (Duruoz hand index (DHI), grip strength). Patients were segregated by mean MCP extension (<20, 20-40, 40-60, and >60 degrees) for MRI scanning. Patients in the four groups were compared using ANOVA for clinical features and MRI tissue measurements (tenosynovial, skin, and fascia thickness). We performed multiple linear regression for determinants of MCP extension.Of 237 patients (90 males), 79 (33•8%) with cheiroarthropathy had MCP extension limitation (39 versus 61 degrees, p<0•01). Groups with limited MCP extension had higher DHI (1•9 vs 0•2) but few (7%) had pain. Height, systolic blood pressure and nephropathy were associated with mean MCP extension. Hand MRI (n=61) showed flexor tenosynovitis in four and median neuritis in one. Groups with MCP mobility restriction had the thickest palmar skin; tendon thickness or median nerve area did not differ. Only mean palmar skin thickness was associated with MCP extension angle on multiple linear regression.Conclusions: Joint mobility limitation was quantified by restricted mean MCP extension, and had structural correlates on MRI. These can serve as quantitative measures for future associative and interventional studies.